PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN OPERATING CAPACITY TERHADAP FINANCIAL DISTRESS - Made Dwi Maharani Putri; I Dewa Ayu Kristiantari; I Made Aditya Paramartha (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2024)
This study is entitled The Effect of Managerial Ownership, Institutional Ownership, Company Size, and Operating capacity on Financial Distress. The formulation of the problem in this study is whether Managerial Ownership, Institutional Ownership, Company Size, and Operating Capacity affect Financial Distress. This study aims to examine the effect of Managerial Ownership, Institutional Ownership, Company Size, and Operating Capacity on Financial Distress. The sample of this study is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. Sampling in this study used purposive sampling technique and obtained 14 companies that met the criteria specified as samples... While the variables of Institutional Ownership and Company Size have no negative and insignificant effect on Financial Distress.